PENGEMBANGAN BAHAN AJAR DIGITAL PADA MATERI KERAGAMAN BUDAYA BERBANTUAN BOOK CREATOR DI KELAS IV SD - Cindyana Putri, Yuliani; Sofwan, Muhammad; Sholeh , Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop digital teaching materials assisted by Book Creator on cultural diversity material for fourth grade elementary school students and to determine their validity and practicality. This research employed the Research and Development (R&D) method using the 4D development model, consisting of define, design, develop, and disseminate stages. The research subjects included media experts, material experts, and fourth grade students. Data collection techniques used validation sheets and student response questionnaires. The results showed that the digital teaching materials assisted by Book Creator were categorized as very valid and very practical. Therefore, these digital teaching materials are feasible to be used as an alternative learning resource in Pancasila Education learning at elementary schools.